Epigenetic modifying enzyme expression in asthmatic airway epithelial cells and fibroblasts. Issue 1 (December 2017) - Stefanowicz, Dorota; Ullah, Jari; Lee, Kevin; Shaheen, Furquan; Olumese, Ekiomoado; Fishbane, Nick; Koo, Hyun-Kyoung; Hallstrand, Teal; Knight, Darryl; Hackett, Tillie-Louise
Abstract Background Recognition of the airway epithelium as a central mediator in the pathogenesis of asthma has necessitated greater understanding of the aberrant cellular mechanisms of the epithelium in asthma. The architecture of chromatin is integral to the regulation of gene expression and is determined by modifications to the surrounding histones and DNA. The acetylation, methylation, phosphorylation, and ubiquitination of histone tail residues has the potential to greatly alter the accessibility of DNA to the cells transcriptional machinery. DNA methylation can also interrupt binding of transcription factors and recruit chromatin remodelers resulting in general gene silencing. Although previous studies have found numerous irregularities in the expression of genes involved in asthma, the contribution of epigenetic regulation of these genes is less well known. We propose that the gene expression of epigenetic modifying enzymes is cell-specific and influenced by asthma status in tissues derived from the airways. Methods Airway epithelial cells (AECs) isolated by pronase digestion or endobronchial brushings and airway fibroblasts obtained by outgrowth technique from healthy and asthmatic donors were maintained in monolayer culture. RNA was analyzed for the expression of 82 epigenetic enzymes across 5 families of epigenetic modifying enzymes. Western blot and immunohistochemistry were also used to examine expression of 3 genes. Results Between AECs and airway fibroblasts, we identified cell-specific gene expression in each of the families of epigenetic modifying enzymes; specifically 24 of the 82 genes analyzed showed differential expression. We found that 6 histone modifiers in AECs and one in fibroblasts were differentially expressed in cells from asthmatic compared to healthy donors however, not all passed correction. In addition, we identified a corresponding increase in Aurora Kinase A (AURKA) protein expression in epithelial cells from asthmatics compared to those from non-asthmatics. Conclusions In summary, we have identified cell-specific variation in gene expression in each of the families of epigenetic modifying enzymes in airway epithelial cells and airway fibroblasts. These data provide insight into the cell-specific variation in epigenetic regulation which may be relevant to cell fate and function, and disease susceptibility.